Analisis Dimensi Hak Asasi Manusia Terhadap Putusan Hakim dalam Perkara Pencabulan Anak di Bawah Umur (Analisis Konten: Perkara No. 166/PID.B/2006/PN PDG) - ., Akmal; Frinaldi, Aldri (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2011)
The purpose of this study was to review the judge’s verdict on case No. 166/PID.B/2006/PN PDG in terms of: (1) whether the judge’s verdict fulfills the elements of legal certainty, fairness, and benefit, (2) whether the judge’s verdict relies on the national and international human rights instruments as well as reviewing the aspects of violations of human rights particularly in cases of child abuse. The type of the human rights cases is domestic abuse of under-aged girls. This research used qualitative method with normative judicial approach. Data processing is done using content analysis. The conclusion of the research; (1) Council of Judges needs to understand the ratification of the Child Protection Law and Law on the Elimination of Domestic Violence as well as the International Human Rights Instruments by the Government of the Republic of Indonesia relating to the Convention on Children’s Rights, in order to stress the domestic child abuse as a form of violation against human rights and as a crime against humanity, (2) in order to protect the victims of domestic violence, particularly women and girls, judges should implement the Child Protection Law and Law on the Elimination of Domestic Violence in their verdicts and the Convention of Children’s Right, because the Penal Code KUHP has not guaranteed fully the protection of children and women as primary victims of domestic violence. Key words: human rights, council of judges.